Development of associations among central adiposity, adiponectin and insulin sensitivity from adolescence to young adulthood - Rasmussen-Torvik, L. J. (2012)
OBJECTIVE: To examine associations of central adiposity, serum adiponectin and clamp-derived insulin sensitivity in a single longitudinal cohort from early adolescence to young adulthood. METHODS: The cohort was examined three times at mean ages 15 years (n = 308), 19 years (n = 218) and 22 years (n = 163). Insulin sensitivity was measured with the euglycaemic hyperinsulinaemic clamp. Circulating adiponectin was measured by enzyme-linked immunosorbent assay. Computed tomography scans were used at mean age 22 years to compute subcutaneous and visceral abdominal fat volume. Partial Pearson correlations and linear regression were used to examine cross-sectional associations at each examination. RESULTS: The moderate negative correlation between waist circumference and adiponectin was significant and essentially unchanged from mean age 15 years (−0.32, P < 0.0001) to mean age 22 years (−0.29, P < 0.002), whereas the negative correlation between waist circumference and insulin sensitivity and the positive correlation between adiponectin and insulin sensitivity increased steadily in magnitude to mean age 22 years (−0.29, P = 0.0002; and 0.32, P < 0.0001, respectively). In regression models including both visceral and subcutaneous fat, only visceral fat was significantly associated with insulin sensitivity, while only subcutaneous fat was nearly significantly associated with adiponectin. CONCLUSIONS: This study shows that the significant negative relationship between waist circumference and adiponectin predated the development of significant relationships between insulin sensitivity and both waist circumference and adiponectin. It also shows that adiponectin is more closely related to subcutaneous fat and insulin sensitivity is more closely related to visceral fat in young adults.